The role of non-bank financials in the formation of long-term resources for economic growth in Russia - Elena Vladimirovna Travkina; Elena Petrovna Ternovskaya; Alim Borisovich Fiapshev (Economies, 2022)
The development of the activities of non-bank financial institutions that accumulate the resources of the national savings system on a long-term basis is seen as a factor in increasing investment in the Russian economy and its growth rates. When carrying out the study, we used general scientific methods, methods of structural, weigh, and dynamic analysis, and comparisons of performance indicators of non-bank financial institutions. Problems in the activities of organizations in the non-banking sector of the Russian financial market are predetermined by the parameters and trends in the development of the socio-economic situation in Russia, including insufficient efficiency of regulatory practices. The positive dynamics of the development of non-bank financial intermediaries is qualified as unstable; it is not supported by the solution of the structural and institutional problems of the Russian economy. In view of this, an increase in their role in the redistribution process is associated both with decisions of a more general order and with the improvement of the regulatory and supervisory practices implemented by the Bank of Russia. The solution to the identified problems in the development of the non-banking segment of the financial market should be aimed at turning it into an effective mechanism for capital formation to ensure economic growth.
Keywords: 330; financial intermediaries; financial market; investment activity; national savings system; non-bank financial institutions